Intranasal trivalent candidate vaccine elicits broad humoral and cellular immunity against pneumococcal pneumonia - Fangyu Ren; Fangyu Ren; Luyun Huang; Luyun Huang; Shilu Luo; Shilu Luo; Changjin Liu; Changjin Liu; Xianlian Chen; Xianlian Chen; Xin Yao; Xin Yao; et al. (Frontiers in Cellular and Infection Microbiology)
Streptococcus pneumoniae is an important pathogen causing public health problems worldwide. Existing pneumococcal vaccines provide protection against only a few of the more than 100 pneumococcal serotypes, highlighting the urgent need for new preventive strategies. Pneumococcal protein vaccines have attracted considerable attention owing to their favorable immunogenicity and antigen conservation, and have demonstrated protective potential against non-serotype-dependent infections. Mice immunized with a trivalent vaccine targeting protein PepN, PepO, and SPD_1609 elicited a robust humoral immune response, as well as Th1, Th2, and Th17 cellular immune responses. The antiserum derived from the trivalent vaccine significantly inhibited Streptococcus pneumoniae adhesion to A549 cells, reduced pneumococcal colonization in the nasopharynx, and improved lung tissue damage and inflammatory responses compared to the monovalent or bivalent vaccine group. In terms of in vivo protection, the trivalent vaccine significantly increased the survival rate of infected mice. The findings suggest that the trivalent vaccine targeting PepN, PepO, and SPD_1609 is a promising multivalent vaccine candidate against Streptococcus pneumoniae.